Prospects for optimizing the drying process of Virginia 202 tobacco leaves - E. Е. Ulyanchenko; N. N. Vinevskaya (Новые технологии, 2021)
Cultivation and use of Virginia 202 broadleaf skeletal variety for the production of smoking tobacco has broad prospects. Problems of post-harvest processing of large leaves with a massive midrib consist in high energy costs with an artificial drying method or the provision of facilities for long-term natural drying. The aim of the research is to apply physical method of cutting the leaf midrib to intensify drying and to determine the effect of this technique on the quality indicators of raw materials. It has been found that the technique of cutting the midrib on the Virginia 202 variety contributes to a significant optimization of the drying process without reducing the quality of raw materials. The drying time of leaves with the combined method is reduced by 2,8 times, with the natural method – by 2,3 times, and the quality indicators of raw materials improve. Commercial quality is characterized by the yield of 1 commercial grade, for combined drying the yield of 1 grade has increased in comparison with the control sample by 27% and amounted to 86,5%, with natural drying – the increase in yield is 4%. Cutting the midrib increases the fiber yield by 3–5% and contributes to an increase in the volumetric-elastic properties of the fiber, providing an economical consumption of raw materials for the production of smoking articles, the consumption is 676,8–753,8 g/1000 pcs. The gustatory quality improves, raw materials with a cut midrib have optimal values of the ratio of carbohydrate-protein balance in the range of 1,08–1,5, the strength is preserved due to the lower consumption of nicotine during the shorter drying period, in comparison with drying the leaf without cutting the midrib. Cutting the midrib in Virginia 202 is cost effective.